Mekanisme Pasar dan Penetapan Harga dalam Perekonomian Islam (Studi Analisis Pemikiran Ibn Taimiyah) - Kendro Pratomo; Trisna Taufik (ITB AAS INDONESIA Surakarta, 2018)
In the 13th century AD Islamic thinkers emerged in many fields of scientific discipline. Among them appeared Ibn Taimiyah who is an Islamic figure who developed many disciplines in certain fields, each in the field of economics. In his mind many things are related to microeconomics and macroeconomics and the problems that occur at that time. And he founded in terms of social and fiqh (Islamic) aspects. Ibn Taimiyah did a lot of discussions about care and regulating prices by the government at that time. He also stated that in strong conditions between demand and supply. He also realizes that if the preparation of goods will diminish, it will increasingly affect the price of the item. Therefore, it is very important to see the relationship between price and supply.